2000
DOI: 10.2337/diacare.23.9.1401
|View full text |Cite
|
Sign up to set email alerts
|

Association of postprandial hypertriglyceridemia and carotid intima-media thickness in patients with type 2 diabetes.

Abstract: OBJECTIVE -Serum triglyceride levels are important in the development of atherosclerosis. Although triglyceride levels are generally increased in the postprandial periods, the association between postprandial triglyceride (pTG) levels and atherosclerosis has not been investigated in diabetic patients. To investigate the role of pTG levels in atherosclerosis, we examined the correlation between pTG levels and carotid intimal-medial thickness (IMT).RESEARCH DESIGN AND METHODS -Carotid IMT was measured by ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
2
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 21 publications
(26 reference statements)
9
107
2
6
Order By: Relevance
“…CML probably emerged as an indicator sensitive to PPG because oxidative stress enhanced in the postprandial period increased the rate of degradation of fructosyl-lysine to CML. Although we observed a strong relationship between urinary levels of dityrosine and mean glucose levels, the limited data on oxidative stress in this study, including measurement of 3-NT, dityrosine, and MetSO, did not confirm this hypothesis, although many other independent studies have shown that postprandial hyperglycemia and hyperlipidemia enhances oxidative stress (27)(28)(29)(30)(31). These findings are in contrast to the relative insensitivity of the Amadori product, represented by fructosyl-lysine residues of Hb or A1C (N␣-fructosyl-valine ϩ fructosyl-lysine residues), which were not significantly decreased by lispro treatment (Table 3 and [21]).…”
Section: Correlations Between Indicators Of Glycemic Control and Plascontrasting
confidence: 49%
See 1 more Smart Citation
“…CML probably emerged as an indicator sensitive to PPG because oxidative stress enhanced in the postprandial period increased the rate of degradation of fructosyl-lysine to CML. Although we observed a strong relationship between urinary levels of dityrosine and mean glucose levels, the limited data on oxidative stress in this study, including measurement of 3-NT, dityrosine, and MetSO, did not confirm this hypothesis, although many other independent studies have shown that postprandial hyperglycemia and hyperlipidemia enhances oxidative stress (27)(28)(29)(30)(31). These findings are in contrast to the relative insensitivity of the Amadori product, represented by fructosyl-lysine residues of Hb or A1C (N␣-fructosyl-valine ϩ fructosyl-lysine residues), which were not significantly decreased by lispro treatment (Table 3 and [21]).…”
Section: Correlations Between Indicators Of Glycemic Control and Plascontrasting
confidence: 49%
“…In recent studies we have found that postprandial methylglyoxal levels are significantly decreased by treatment with nateglinide in type 2 diabetes (37), suggesting that decreases in methylglyoxalderived AGEs may also occur with other treatments targeting postprandial glycemia. Since postprandial increases in ␣,␤-dicarbonyls and their associated AGEs can lead to direct cellular damage, decreasing their levels with lispro as well as decreasing postprandial oxidative lipemia and oxidative stress (27)(28)(29)31,38) could potentially lead to a reduction in longterm vascular complications.…”
Section: Correlations Between Indicators Of Glycemic Control and Plasmentioning
confidence: 99%
“…Postprandial hypertriglyceridemia may represent an independent predictor of CVD in nondiabetic patients 2 and may be a predictor of carotid intima-media thickness in patients with type 2 diabetes. 22 However, recent studies support the hypothesis that postprandial hyperglycemia also is a risk factor for CVD. 23 The concept that postprandial hypertriglyceridemia and hyperglycemia may be important factors for the development of CVD is supported by evidence that both induce endothelial dysfunction, 6 -9 whereas there is a broad consensus that abnormalities of endothelium-dependent arterial relaxation are an early marker of atherosclerosis 4 and may predict CVD.…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, a number of studies have shown that postprandial lipaemia is linked to endothelial dysfunction and generation of oxidative stress in patients with T2Dm [13,14], that are well-established factors in the pathogenesis of atherosclerosis. In addition, a correlation between carotid intima-medial thickness and postprandial hypertriglyceridaemia has been shown despite normal fasting TGs [15]. Thus, the characteristics of postprandial lipid metabolism may be relevant for the development of atherosclerosis in patients with T2Dm.…”
Section: Introductionmentioning
confidence: 99%